CONDUCIVE YOGA EDUCATION AND PSYCHOSOCIAL WELLBEING - PRIYA, T.; NEETHU, P R.; MURALIRAJAN, K. (International Journal of Psychosocial Rehabilitation, 2020)
The main Statement of this study to analysis the conducive yoga education and psychosocial wellbeing of the young and promoting society. The study finalised the result the yoga education that made signified result and support the study. It was concluded that yoga education has been spending goodness in the psychosocial wellbeing.